Risk factors for brain metastases in surgically staged IIIA non-small cell lung cancer patients treated with surgery, radiotherapy and chemotherapy - Petrović Marina; Ilić Nevenka; Lončarević Olivera; Čekerevac Ivan; Lazić Zorica; Novković Ljiljana; Ćupurdija Vojislav; Kostić Gordana (Vojnosanitetski Pregled)
Introduction/Aim. Lung cancer is a leading cause of mortality among patients with carcinomas. The aim of this study was to point out risk factors for brain metastases (BM) appearance in patients with IIIA (N2) stage of nonsmall cell lung cancer (NSCLC) treated with three-modal therapy. Methods. We analyzed data obtained from 107 patients with IIIA (N2) stage of NSCLC treated surgically with neoadjuvant therapy. The frequency of brain metastases was examined regarding age, sex, histological type and the size of tumor, nodal status, the sequence of radiotherapy and chemotherapy application and the type of chemotherapy. Results. Two and 3-year incidence rates of BM were 35% and 46%, respectively. Forty-six percent of the patients recurred in the brain as their first failure in the period of three years. Histologically, the patients with nonsquamous cell lung carcinoma had significantly higher frequency of metastases in the brain compared with the group of squamous cell lung carcinoma (46% : 30%; p = 0.021). Examining treatment-related parameters, treatment with taxane-platinum containing regimens was associated with a lower risk of brain metastases, than platinum-etoposide chemotherapy regimens (31% : 52%; p = 0.011). Preoperative radiotherapy, with or without postoperative treatment, showed lower rate of metastases in the brain compared with postoperative radiotherapy treatment only (33% : 48%; p = 0.035). Conclusion. Brain metastases are often site of recurrence in patients with NSCLC (IIIA-N2). Autonomous risk factors for brain metastases in this group of patients are non-squamous NSCLC, N1-N2 nodal status, postoperative radiotherapy without preoperative radiotherapy.